Wine fermentation process monitoring system - BAI YUNFU; PAN HUI (2015)
The invention discloses a wine fermentation process monitoring system comprising a monitoring mode which is electrically connected with a ZigBee coordinator. The ZigBee coordinator is connected with a processor through a wire. The processor is connected with a voice chip and a memory through wires. Problems caused by the fact that the environmental parameters of liquor fermentation are mainly read, gathered and analyzed in an artificial manner currently, for example, a waste of labor is caused, the error rate is high, the real-time performance is poor, and industrialized production of liquor is not facilitated, are solved.